Permeable Boundaries: Negotiation, Resistance, and Transgression of Street Space in Saint-Henri, Quebec, 1875-1905 - Lord, Kathleen (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2005)
In late-nineteenth- and early-twentieth-century Saint-Henri, the street was a contested space. The local elite's municipal management of public space conflicted with the popular social use of the streets, both in the design and promotion of the main commercial street, rue Notre-Dame, and in the moral regulation of street behaviour. Political negotiation was limited to male property owners, for restrictions on the municipal franchise in a bourgeois liberal democracy excluded most women, many tenants, and all street vagrants. Mounting public debt resulting from the promotional politics of expropriation and bonusing incited popular resistance and, in 1905, led to annexation to the city of Montreal. The local elite directed the use of public space in ways that conformed with their private perspectives. Local by-laws and policing efforts largely succeeded in eliminating or displacing criminal and disruptive behaviour on rue Notre-Dame by day, but nightly disturbances and illicit activities were common on adjoining residential streets, in hidden areas, and in the neighbouring community of Sainte-Cunégonde. A wider range of primary sources, including photographs and sketches, are crucial to disclosing the class and gendered nature of street life.